The Relationship Between Organizational Commitment And Employee Turnover Intention - Ting, Wennie Shi Han (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study is aimed at determining the relationship between organizational commitment (affective commitment, continuance commitment, normative commitment) and employee turnover intention. This research was done by using quantitative approach whereas the data were collected by using questionnaire as the instrument. Besides that, the data was collected from 55 samples in one of the manufacturing company in Kuching, Sarawak. The data were then analyzed and interpreted by using descriptive statistics and inferential statistics. Statistical Package for Social Sciences (SPSS) version 20.0 had been used in data analysis process. Pearson Correlation Coefficient and Multiple Regression Analysis were used to measure the relationship between the independent variables and dependent variables. As the result, the findings show that there is a significant relationship between organizational commitment and employee turnover intention. Then, it was found out that the affective commitment is the most dominant factor that would affect the employee turnover intention. The results of present study had recommended a focus that may guide the organizations and future researchers.